2020
DOI: 10.1039/d0cc02598d
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-catalysed transfer hydrogenation of esters

Abstract: A manganese complex of a tridentate P,N,N ligand can catalyse the reduction of esters using ethanol as the reductant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…In 2020, Clarke and co-workers reported the first example of TH of ester catalyzed by a ferrocene-based Mn(I) complex using ethanol as the H2-donor (Figure 2). [30] The catalytic system displayed high activity and the catalyst loading could be reduced to 1 mol% at 100 °C in the presence of tBuOK (20 mol%). Good tolerance to halogen and heterocycles was observed, whereas the presence of cyano or amino group was detrimental to the activity.…”
Section: Reduction Of Carboxylic Acid Derivativesmentioning
confidence: 99%
“…In 2020, Clarke and co-workers reported the first example of TH of ester catalyzed by a ferrocene-based Mn(I) complex using ethanol as the H2-donor (Figure 2). [30] The catalytic system displayed high activity and the catalyst loading could be reduced to 1 mol% at 100 °C in the presence of tBuOK (20 mol%). Good tolerance to halogen and heterocycles was observed, whereas the presence of cyano or amino group was detrimental to the activity.…”
Section: Reduction Of Carboxylic Acid Derivativesmentioning
confidence: 99%
“…In 2020, Clarke et al reported that catalyst 37 could be used for the double transfer hydrogenation of ester to give alcohols. [130] The reduction of C-N -bonds was demonstrated independently by the groups of Khusnutdinova and Sortais in 2019. [131] Both Aldehydes and Imines could be reduced in high yield by catalysts 46 and 50.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[132] Scheme 20: Part A: Transfer hydrogenation catalysts for the reduction of aldehydes, imines, esters, and N-heterocycles. (For Clarke et al 2020 catalyst 37: Ar = 3,5-dimethyl-4-methoxybenzene) [130] Part B: reductive cross-coupling of N-heterocycles with an asymmetric Mn(I) base activated transfer hydrogenation catalyst. Part C: Switchable primary and secondary amine products from the transfer hydrogenation of nitriles using SNN-based manganese catalysts.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, this strategy is mainly limited to the reduction of ketones [55][56][57] and esters. 21,[58][59][60] Most recently, significant contributions were made in the transfer hydrogenation of amides. [61][62][63] Klankermayer and co-workers reported an efficient Ru-catalyzed transfer hydrogenation of cyclic amides to cyclic tertiary amines, 61 while the groups of Xu, Fan and Xiao reported the Ru- 62 and B(C 6 F 5 ) 3 - 63 catalyzed reduction of aliphatic amides to amines.…”
Section: Introductionmentioning
confidence: 99%